The effect of pulsed electron beam melting on microstructure, friction and wear of WC–Hadfield steel hard metal; Wear; Vol. 257, iss. 1-2 - Gnyusov S. F. Sergey Fedorovich; Tarasov S. Yu. Sergei Yulievich; Ivanov Yu.; Rothstein V. (2004, 2004)
Title screen